Simulasi Kegiatan Jual Beli Dan Menabung Bagi Siswa Siswi TK Al Azhar 54 Pekanbaru - Dewi Martha (Jurnal Pengabdian Masyarakat Indonesia Sejahtera, 2023)
Simulation of buying, selling and saving activities motivated by the needs of young children, especially students at Kindergarten Al Azhar 54 Pekanbaru in improving ability to recognize the concept of numbers because currently it is still using the assignment method, books and using general learning media cause young children difficult in understanding concept of numbers and number symbols. Several methods were applied, namely: observation, interviews, counseling and documentation. The PKM activities are simulation of buying and selling activities to provide education on buying and selling activities that are often do in daily life, simulations of saving activities at bank, counseling the benefits of saving at bank and explanations bank products. The expected final result of this PKM activities are Al Azhar 54 Pekanbaru Kindergarten students can improve their ability to recognize numbers and number symbols, know the value of money, understand buying and selling transactions in daily life, increase their knowledge about banks, knowing how to save at bank, motivate to save from an early age to buy favorite items, training discipline in using money according to needs, and teaching not to spend all the money you have so that it is easier to manage your finances.